'BARI Masur‐8': A high‐yielding and biofortified lentil cultivar in Bangladesh. Issue 3 (25th June 2022) - Shahin Uz Zaman, Md; Altaf Hossain, Md; Alam, Md Jahangir; Mahbubul Alam, AKM; Ali, Md Omar; Sarker, Debasish; Sarker, Ashutosh
Abstract: Lentil ( Lens culinaris Medik.) is a nutritious food for millions of people globally. It plays an important role in Bangladesh as a good source of protein and micronutrients for low‐income populations with less access to animal protein. To enhance nutritional security, a nutrient‐dense lentil line, LR‐9‐25, was identified from a Stemphylium blight (SB) screening population developed at The International Center for Agriculture Research in the Dry Areas through a cross between ILLX955‐135 and FLIP92‐52L. The line LR‐9‐25 was rigorously evaluated in diverse agro‐ecological conditions of Bangladesh and released for commercial cultivation by the Pulses Research Centre, Bangladesh Agricultural Research Institute as 'BARI Masur‐8' (Reg. no. CV‐35, PI 700306) in 2015. BARI Masur‐8 matures in 115–120 d and fits well into existing rice‐based cropping patterns. It is a medium‐height (35 cm) and medium‐seeded (1.94 g 100 −1 seed) cultivar having a high level of tolerance to SB and root rot diseases. BARI Masur‐8 showed high yield potential (1, 973 kg ha −1 ) and high concentrations of Fe (74 mg kg −1 ), Zn (61 mg kg −1 ), and Se (325 μg kg −1 ) in seed. Another desirable trait is the late planting potential, with sowing up to the first week of December after the harvest of long‐duration rice ( Oryza sativa L.) cultivars, which is a major area for lentil production in Bangladesh. The cultivation of this improved cultivar will play an important role for enhancing nutritional security by increasing lentil production in Bangladesh, Nepal, and eastern Indian states in South Asia. Core Ideas: High‐yielding (1, 973–2, 500 kg ha −1 ) lentil cultivar BARI Masur‐8 outyielded BARI Masur‐7 by 20–25%. BARI Masur‐8 seed is enriched with Fe (74 mg kg −1 ), Zn (61 mg kg −1 ), and Se (325 μg kg −1 ). BARI Masur‐8 is tolerant to stemphylium blight and root rot diseases. BARI Masur‐8 has late planting potential after the harvest of long‐duration rice cultivars.